1999
DOI: 10.1152/ajprenal.1999.276.2.f271
|View full text |Cite
|
Sign up to set email alerts
|

Kinin influences on renal regional blood flow responses to angiotensin-converting enzyme inhibition in dogs

Abstract: The relative roles of ANG II and bradykinin (BK) in the regulation of renal medullary circulation have remained unclear. We compared the contributions of ANG II and BK to the renal medullary blood flow (MBF) responses to angiotensin-converting enzyme (ACE) inhibition (enalaprilat, 33 μg ⋅ kg−1 ⋅ min−1) in dogs maintained on a normal-salt diet (0.63%, 3 days, n = 14; group 1) with those fed a low-salt diet (0.01%, 5 days, n = 14; group 2), which upregulates both the kallikrein-kinin and the renin-angiotensin sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 19 publications
4
32
0
Order By: Relevance
“…Moreover, mainly due to the use of icatibant, a specific B 2 receptor antagonist, the contribution of kinins in the cardiovascular effects of ACE inhibitors has been documented experimentally, both on in vitro formation of endothelial nitric oxide and in vivo hypotensive and antihypertensive actions in animals (Linz et al 1995). Bradykinin also contributes to the renal vasodilator response to ACE inhibition (Fenoy et al 1991;Omoro et al 1999). Finally, in the isolated perfused rat kidney, we have reported that bradykinin is a potent renal vasodilator, the effects of which are potentiated by ACE inhibitors (Bagaté et al 1999a(Bagaté et al , 1999b.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, mainly due to the use of icatibant, a specific B 2 receptor antagonist, the contribution of kinins in the cardiovascular effects of ACE inhibitors has been documented experimentally, both on in vitro formation of endothelial nitric oxide and in vivo hypotensive and antihypertensive actions in animals (Linz et al 1995). Bradykinin also contributes to the renal vasodilator response to ACE inhibition (Fenoy et al 1991;Omoro et al 1999). Finally, in the isolated perfused rat kidney, we have reported that bradykinin is a potent renal vasodilator, the effects of which are potentiated by ACE inhibitors (Bagaté et al 1999a(Bagaté et al , 1999b.…”
Section: Discussionmentioning
confidence: 98%
“…In a sodium depleted organism plasma renin activity and plasma angiotensin II increases [17,18] and it may result vasoconstriction. However, cyclooxygenase expression [17,47] and kallikrein-kinin system activation [48,49] increases and these vasodilator agents may counterbalance the vasoconstriction produced by angiotensin II. As percent changes of blood flow and vascular resistance after NOS blockade does not differ significantly from those ones observed in normal rats we suppose that NO system has no role in adaptation of intrarenal blood flow in sodium restricted rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, kinins contribute to the renal vasodilatory actions of ACEIs, mainly in the medullary circulation [69][70][71][72][73].…”
Section: Angiotensin Converting Enzyme Inhibitorsmentioning
confidence: 99%